No-trade in the laboratory - Marco Angrisani; Antonio Guarino; Steffen Huck; Nathan Larson (Center for Economic Studies and ifo Institute (CESifo), 2008)
We test the no-trade theorem in a laboratory financial market where subjects can trade an asset whose value is unknown. Subjects receive clues on the asset value and then set a bid and an ask at which they are willing to buy or to sell from the other participants. In treatments with no gains from trade, theory predicts no trading activity, whereas, in treatments with gains, trade becomes theoretically possible. Our experimental results show that subjects fail to reach the no-trade equilibrium by pure introspection, but they learn to approach it over time, through market feedback and learning.
Keywords: C92; D8; G12; G14; 330; No-trade theorem; experiment; Wertpapierhandel; Tausch; Börsenspiel; Test; Lernprozess